Export market shares: A trivial concept? - Klaus Vondra (FIW - Research Centre International Economics, 2017)
The European Commission and euro area central banks use different methods to calculate export market shares and rely on different data sources to do so. Thus, the resulting evidence varies considerably over time, prompting different economic policy conclusions with respect to the development of export competitiveness - which is an undesirable fact. This paper presents methods and data sources used to derive export market shares with a view to explaining these differences. We conclude that the export market share concept is trivial only at a first glance because it can be implemented in a number of ways none of which would appear to be the single best practice.
Keywords: F14; F40; H12; 330; export market shares; conceptual and data differences